Influence of Enzyme Concentration and Hydrolysis Time on Soluble Protein Content of Protein Hydrolysate Prepared from Apple Snail (Pila ampullaceal) - Andre Yusuf Trisna Putra; Dedin Finatsiyatull Rosida; Anugerah Dany Priyanto (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
The objective of this study was to evaluate soluble protein content of protein hydrolysates obtained by enzymatic hydrolysis of apple snail using a trypsin enzyme. Apple snail were collected from traditional market at Pabean-Sidoarjo. Trypsin enzyme was used in enzymatic hydrolysis. The two variables, enzyme/substrate (E/S) ( 0.01, 0.05, 0.1) ratio and hydrolysis time (3 h, 6 h, 9 h, 12 h, 15 h, 18 h) and was used to produce the apple snail hydrolysate. The result showed that soluble protein content was about 2.3%-4.52%. The increase E/S ratio and hydrolysis time, the higher soluble protein content values was. The highest total soluble protein was achieved E/S 0.1 ratio at 12 h, 4.52%. But, after 12 h hydrolysis time, soluble protein was decreased. Optimum treatment to hydrolyzing apple snail using trypsin enzyme was E3H4 treated (E/S 0.1 ratio and 3 h)